Food and nutrition education actions in school environment: a scoping review (Research, Society and Development, 2023)
For a great portion of the child population, the school can be a powerful environment that promotes health, since actions in schools facilitate access for schoolchildren. It is relevant to investigate whether such actions are in line with current dietary guidelines, as recommended. Objective: To analyze the scientific production about actions of Food and Nutrition Education after the current publication of the Dietary Guidelines for the Brazilian Population. Methods: A scoping review was done using the methodological procedures proposed by the Joanna Briggs Institute, and the structure as per recommendation of the PRISMA-ScR. The research occurred in the PubMed database, Virtual Health Library and Embase and considered studies published after 2014, when the Dietary Guidelines for the Brazilian Population was published, that mentioned actions of Food and Nutrition Education for the Brazilian scholars. Results: Eighteen articles considered relevant to this review were included. All the studies proposed interventions, despite of the different methodological designs. The studies presented great diversity in the intervention design (frequency, duration, technique, resources and themes). The majority used the Dietary Guidelines for the Brazilian Population as theoretical content reference, but only half of them highlighted the pedagogical premises practiced. Conclusion: Gaps were evidenced in the theoricalmethodological development of Food and Nutrition Education actions in the school environment and the limited use of tools such as the Dietary Guidelines for the Brazilian Population. In light of the findings, an educational product was built in video format, which aims to support and encourage professionals to carry out these actions.